A quantitative analysis of the Quality of Service of Short Message Service in the Philippines - Canlas, Marnelli (Archīum Ateneo, 2011)
We report the first measurements of the Quality of Service of Short Message Service provided by the three carriers in the Philippines where prepaid 2G systems are running at 90% capacity most of the time. We measured message completion rate, delay times, and billing accuracy for both ordinary and high density traffic cases. From these, we developed a figure of merit for the QoS as a product of the average Network QoS and Billing QoS. We observed that an SMS takes about 4 seconds to as long as 1 hour, 36 minutes from sending to receiving, depending on the network state. Average cost per message also varies widely from P0.50 to P27, with P1.00 being the nominal agreed rate. We clearly show that under high-intensity traffic cases, some messages are dropped. Using the QoS formula, we are able to, both quantitatively and qualitatively, compare the performance of the carriers.